IMPLEMENTASI NILAI – NILAI KARAKTER DALAM PROSES PEMBELAJARAN PPKN BAGI PESERTA DIDIK DI SMA N 1 HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Yozia Fitri; Buchari Nurdin; Ranti Nazmi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research is motivated by several problems, namely: There are still many students who violate the rules of values and norms that apply in schools and society. This study aims to describe the character education design that will be prepared by the teacher and implement the character education design for students as well as describe the constraints that exist in the form of implementing the character education.The type of research used in this research is qualitative with descriptive method and the informants are PPKn subject educators, students of class XI IPS 1 and XI IPS 2. Data collection techniques and tools are observation, interviews and documentation. Data analysis techniques with data reduction, presenting data and drawing conclusions